2007
DOI: 10.1029/2007jg000443
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling spatio‐temporal variation in carbon dioxide efflux from surface litter, roots, and soil organic matter at four rain forest sites in the eastern Amazon

Abstract: 1] This study explored biotic and abiotic causes for spatio-temporal variation in soil respiration from surface litter, roots, and soil organic matter over one year at four rain forest sites with different vegetation structures and soil types in the eastern Amazon, Brazil. Estimated mean annual soil respiration varied between 13-17 t C ha À1 yr À1 , which was partitioned into 0-2 t C ha À1 yr À1 from litter, 6-9 t C ha À1 yr À1 from roots, and 5-6 t C ha À1 yr À1 from soil organic matter. Litter contribution s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
3
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(99 citation statements)
references
References 51 publications
8
87
3
1
Order By: Relevance
“…Indeed, potential soil respiration determined on drained samples in the current study showed a clear link to nutrient status. This was not reflected in the pattern of CO 2 flux in the field, however, suggesting that variables other than nutrient status, such as root respiration (Chimner 2004;Metcalfe et al 2007) or water table fluctuations (Jauhiainen et al 2005), regulate the net CO 2 efflux from the peat surface. The CO 2 flux rates were within the range of those measured from lowland forested swamps on deep peat in central Kalimantan, Indonesia (ca.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, potential soil respiration determined on drained samples in the current study showed a clear link to nutrient status. This was not reflected in the pattern of CO 2 flux in the field, however, suggesting that variables other than nutrient status, such as root respiration (Chimner 2004;Metcalfe et al 2007) or water table fluctuations (Jauhiainen et al 2005), regulate the net CO 2 efflux from the peat surface. The CO 2 flux rates were within the range of those measured from lowland forested swamps on deep peat in central Kalimantan, Indonesia (ca.…”
Section: Discussionmentioning
confidence: 97%
“…Root respiration and elevated respiration rates due to labile C inputs from roots contribute to net soil CO 2 emissions (Davidson and Janssens 2006). For example, root respiration contributed between 40 and 60 % from net soil emissions in forests in the Eastern Amazon during the dry season (Metcalfe et al 2007). Therefore, we attribute the decline in CO 2 emissions to loss of respiration from R. taedigera roots, and to the suppression of root exudates, which are to some extent consumed and converted into CO 2 by rhizosphere microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…The plot CAX-06, is a tall primary forest (35 m height canopy) situated on a clay ferralsol (oxisol in USDA soil taxonomy) near a flux tower site ). The CAX-03 plot is a sandier site located 2 km to further south, which was the control plot for a drought experiment (Metcalfe et al, 2007a). The Terra Preta site (CAX-08) is a late successional forest on an ArchaeoAnthrosol (this classification was modified from the WRB soil taxonomy by Kampf et al (2003) to encompass the variability of Terra Preta soils in Amazonia).…”
Section: Study Sitesmentioning
confidence: 99%